Pengukuran Kesenjangan Pengetahuan (K-Gap) Menggunakan Importance and Performance Analysis dan Root Cause Analysis - Suwaebatul Aslamiyah; Amaliasyifa Agustina (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Student communities is an unit which responsible for various activities whether an academic or non-academic activities. The service quality given by student communities has huge impact towards involvement of student into every activities/event held by internal campus or any others campus,  which is in wide specs  affected the value of a  university. The service quality given by Student Communities affected by the knowledge level which  every staff of SC  supposed  to have. The goal of the research is to measure the knowledge gap and to find out the cause. The methods used to measure the value of gap knowledge is IPA, meanwhile the method used to analyzing the problem is RCA. Application of IPA method dividing the level of importance into 4 quadrant, consist of quadrant 1  (Concentrate These), quadrant II (Keep Up The Good Work) , quadrant III (Low Priority) and quadrant IV (Possible Overkill), resulting  total number of 82 % from all of knowledge atributes in quadrant 1 and II , where those atributes is the main focus for enchantment and upgrading of qualities. After analyzing  and finding the problem source using RCA method, it can be concluded that  the Student Communities need a system that contained knowledge datas which is accessible and also facilitate the sharing data process. The researcher concluded that the SC need a KMS. SECI Model then used to make a beta version prototype which is offered as solution of Student Communities' s problems.